Implementation of Talqin, Tafahhum, Tahfidz, and Murojaah Methods In The Tahfidzul Al-Qur'an Program For The Students of University of Darussalam Gontor For Girls Mantingan, Ngawi, East Java - Astuti Sifa’urahmah; Aulia Indah Zahra Ibrahim (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Memorizing Al-Qur'an is a necessity for every Muslim in memorizing letters during the obligatory prayers and sunnah prayers One of the efforts of the Indonesian people is to develop a program of memorizing the Qur'an in formal education including universities. Students are agents of change who are responsible for strengthening society and religion by safeguarding the Qur'an and Sunnah. With the